PARTISIPASI MASYARAKAT DESA NGUWOK KABUPATEN LAMONGAN DALAM MENDUKUNG “POLISI BAIK MENAMPUNG ORANG DENGAN GANGGUAN JIWA” - Rafi Fauzil Akbar; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2025)
Community participation is a process and or participation of a community in activities either actively or passively. The community will first see how important or good and bad the activity will be to do or not do a behavior to participate. Community participation will emerge when the community sees the good side of what they see and get. The purpose of this study was to understand or analyze the response and participation of the Nguwok Village community towards the presence of police who accommodate people with mental disorders in Nguwok Village, Modo District, Lamongan Regency. The data collection technique in the study used in-depth interviews. The data analysis technique used Miles and Huberman's analysis which consisted of the stages of data reduction, data presentation and drawing conclusions. The results of the study showed that community participation would emerge when the community saw the good side of what they saw and got. The response of the Nguwok Village community in supporting the Police to accommodate people with mental disorders used three indicators of attitudes towards behavior, namely defining the understanding of the surrounding community towards the behavior of the Police both accommodating people with mental disorders, conveying protests against behavior because of disturbances and conveying approval of behavior because of benefits. Before the community participates, the community has the intention to participate based on perceived behavioral control where the community feels it is easy to participate in any form, the most important thing is that the community is sincere and does not mind what they want to participate in. With this, the intention to participate arises from the community and with this intention, the behavior of participation arises by the community in the form of thoughts, property, and energy.